PERCEIVED SUSCEPTIBILITY DENGAN TINDAKAN IBU DALAM DETEKSI DINI KANKER SERVIKS DI KELURAHAN MULYOREJO SURABAYA - Rinda Hidayati; Ni Ketut Alit; Retnayu Pradanie (Pediomaternal Nursing Journal, 2014)
Cervical cancer is still being the most deathly cancer disease in women. This disease does not show serious symptoms atthe first time. Many patients have already taken a prescription when they had felt down in the terrible condition. Perceivedsusceptibility is one of component HBM theory women in cervical cancer that can be a key predictor to women to takeearly detection. The aim of this study is to analized the correlation between perceived susceptibility with screeningbehavior cervical cancer in sub district Mulyorejo Surabaya which used cross sectional design. The population is consistthe women in RW 1 sub district Mulyorejo Surabaya and taken by purposive sampling and then according to inclusionsand exclusions criterias founded 106 respondent. The data were collected using questionarries and were statisticallyanalized by Spearman’s Rank Correlation with the level significant of p< 0,05. The results showed that the mostperceived susceptibility in woman was positive consist of 60 respondent (56,6 %) and most of respondent washaven’t been doing screening behavior cervical cancer consist of 58 respondent (54,72%). The results showedthat there was a significant correlation between perceived susceptibility with screening behavior cervical cancer in subdistrict Mulyorejo Surabaya with p value = 0,000 with coefficient correlation (r) is 0,491. It can be concluded that there is acorrelation between perceived susceptibility with screening behavior cervical cancer in sub district Mulyorejo Surabaya.The expectation to next researcher is to find out other variables in HBM theory that have stronger influence to takebehavior in screening cervical cancer